AKULTURASI ARSITEKTUR LOKAL DAN MODERN PADA DESAIN ANTWERPEN-CENTRAAL (ANTWERP CENTRAL) RAILWAY STATION, BELGIA - Aji, Iman; Fauzy, Bachtiar (Jurnal Riset Arsitektur, 2022)
Abstract - The development of the times has an impact on all aspects including developments in the transportation sector, stations that serve passengers in the land transportation sector are also affected by the modernization style. The development of the era in question is modernization, where everyone wants to move quickly and practically. The modern style has an impact on the development of architectural styles, in other words, the shift in the original style of a building is displaced by a new style, namely the modern style. The purpose of this research is to know and understand the concept of acculturation that occurs in the Antwerp station building, to find out the elements that influence it and produce conclusions from the object of study discussed, namely at the Antwerp Centraal Station. The research method used is a qualitative method, which aims to see the value contained in the physical building. Followed by the descriptive method, where the data obtained were collected in accordance with the research conducted which was adapted to the theory used. So that the final result is in the form of a conclusion from the results of the analysis that has been done. The expected benefit is to be able to increase the knowledge and knowledge of the readers of the research that has been carried out by researchers. Keywords: acculturation, architecture, train station building and Antwerp Centraal Station.